The effect of oral performances in audiences' minds and behaviour - Santosa, Santosa (UI Scholars Hub, 2010)
As a means of communicating thoughts, gamelan performances affect the way audiences construct their worldview. More than that, listeners in villages believe that performances can affect people's behaviour. Performances may be deeply influential in the creation of fundamental social values such as in-group integrity, feelings of unity and peace in the community. All this demonstrates that in villages, arts are not autonomous entities; people value the arts as an integral domain with other social activities.